F a b 0 a b f

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: º Öu Ö× Ö ÝØÙÑ Ó x1 , x2 , . . . , xn ÝÖ Ö ÐÐ ÒÒ ÐÙØ Ú ÖØ xi ÖÙÑ Ö ×Ñ ÐÐ Ö ÙÖÒ Ö Ö ÝØÙÒÙÑ t1 , t2 , . . . , tm ∂u ∂u ∂x1 ∂u ∂x2 ∂u ∂xn = + + ··· + . ∂tj ∂x1 ∂tj ∂x2 ∂tj ∂xn ∂tj ÐÐ Ò Ð º Ë Ð Ö ÒÒ º ´ º ÔÓ× Ø Ú ÐÝ ×ÖÚÖ Ø ÐÙ ÓÑÓ f (x1 , x2 , . . . , xn ) ÓÙ× Ó Ö kµ Ö Ö× ØÚÖ Ú ØØ Ò×Ð ØØ ×Ø k Ó ÝÖ Ö × Ö Ú ÖÒ ÔÙÒ Ø (x1 , x2 , . . . , xn ) t>0 f (tx1 , tx2 , . . . , txn ) = tk f (x1 , x2 , . . . , xn ). º Ë ØÒ Ò º Ú ØØ Ò×Ð ØØ ÐÐ f (x1 , x2 , . . . , xn ) k Ö ×Ø n ÙÖ × Ñ ÐÐ Ö ÝÖ×Ø ×Ø × ÐÙØ ÙÖ Ó Ö xi fi (x1 , x2 , . . . , xn ) = kf (x1 , x2 , . . . , xn ). i=1 ¾½º Ò Ö ¾¼¼ ½½ Ê ÒÚ Ð ÙÖ º Å ÐÐ Ö ËØ Ö Ö º¼ Ë Ð Ö Ò Ò º Ö ÝØ ×Ø Ö Ó Ö× ´ Ð ÒÐ ÝÖ Ö ÖÙÑ Ö ØÚÖ º Ä ÒÙÐ ÒÒ ÖÒ Ð Ö Ò Ò ÁÁ Ò Öº Ö ºµ ÓÔÒÙ ÑÖ Ð Ä ØÙÑ Ö ÝØ ×Ø ÐÖ ÒØ f ÚÖ ÐÐ ÒÒ aº ÐÐ f Ð ÒÐ Ø f × × Ð × Ñ ÒÒ Ð ÙÖ ÔÙÒ Ø ÒÒ ÔÙÒ Ø a f ′ (a) = lim Ö Ø Ðº f (a + h) − f (a) h→0 h º¼+ Ë Ð Ö Ò Ò º ÒÒ ÔÙÒ Ø ÒÒ Ö ÝØ ×Ø Ö Ó ´ ÒÒÙÖ Ð ÖÙÑ Ö ØÚÖ Ö ØÐ ÝÖ Ö × ÐÖ Ò × ÐÖ ÔÙÒ Ø Ð ÒØ ÒÐ ØÐ ºµ ÓÔÒÙ Ä ØÙÑ f ÚÖ ÐÐ Ð ÙÖ aº ÐÐ f Ö× L(x) = f (a) + m(x − a) Ð ÒÐ Ø f × Ð × Ñ ÒÒ a ÖØ Ð m ÒÒ f (a + h) − L(a + h) = 0. h→0 h lim ´Ì Ð Ò m Ð Ó Ú Ö ÙÖ ÚÖ ÐÐ Ò f ′ (a)ºµ Ö× ÐÖ ÒØ ÓÔ ÒÒ × ×Ø × ÐÙØ Ù ÙÑ Ú Ö × ÙÖ º½ Ë Ð Ö Ò Ò º ÚÖ ÒÐ Ø ÔÙÒ f (x, y ) × Ñ Ø ÒÙÑ (a, b) (a, b) ÐÖ Ö× Ò Ø Ö Ö ÝÖ×Ø f ÖÙ × (a, b) f (a + h, b + k ) − f (a, b) − hf1 (a, b) − kf2 (a, b) √ = 0. (h,k)→(0,0) h2 + k 2 lim º¾− Ë ØÒ Ò º´Å Ð ÒÙ ÒÒ Ð ÒÐ Ð Ø ×× ØÒ Ò ÓÔÒ Òºµ Ð ÒÙ ÖÙÑ Ö ÝÖ Ö Ö Ø Ð ÔÙÒ ÐÐ [a, b] Ó Ð (a, b)º f× ØÙÖ c ×Ñ ÓÔÒ ÐÐØ ÐÓ Ð ÒÙ (a, b) f (b) − f (a) = f ′ (c)(b − a). º¾ Ë ØÒ Ò º × Ù ´Å Ù Ó Ð ×Ñ Ð ÐÐ ×× ØÒ Ò ºµ Ä ØÙÑ ÒÒ Öº ÖÙÑ Ö f (x, y ) Ú Ù ÝÖ Ö Ö ÖÙ Ó ÐÐ × Ñ Ö× ÐÖ ×Ø × ÒØ ÐÙØ ÓÔ ÒÒ ÙÖ f× ÐÖ Ò Ö h, y + k ) ∈ Dº D Ñ Ñ (a, b) ×× Ö × Ó Ö ÝÖ×Ø h ½ k ÒÒ × Ù Ø ÐÙÖ ÒÒ (x + ÖÙ Ø Ð Ø ÐÙÖ θ1 θ2 Ñ ÐÐ ¼ Ó f (a + h, b + k ) − f (a, b) = hf1 (a + θ1 h, b + k ) + kf2 (a, b + θ2 k ). º¿ Ë ØÒ Ò º (a, b) ×Ñ ÐÐ ÒÒ Öº Ä ØÙÑ Ö ÐÐ f (x, y ) ×× Ö × ÚÖ Ù ÖÙ Ø ÒÐ ÐÐ × Ñ Ö× ÐÖ ×Ø ÒØ × ÓÔ ÒÒ × ÐÙØ ÙÖ Ù Ö ÝÖ×Ø f × D Ñ Ò Ñ Ù ÐÖ ÖÓ f Ð ÝÖ Ö (a, b)º ÐÐ × Ñ Ö Ð ÒÐ Ø ÔÙÒ Ø ÒÙÑ º Ë ØÒ Ò º Ö ÖÙÑ Ö ÐÐØ f (x, y ) × (a, b)º f ×Ñ (a, b)º ½¾ ºÃ ÝÖ Ö ´µ ´ ´ µ ÝÖ×Ø µ ÐÐ ÙÖ Ð º Ó × Ö ×Ø Ó ÙÑ ×Ø Ê ØÙÑ z = f (x, y ) Ö×Ñ x = x(s, t) Ó y = y (s, t)º ÖÙÑ Ö x(a, b) = p f ÐÙØ Ð × y (a, b) = q ÙÖ x(s, t) ÒÐ ÐÙ...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online